Beyond Newgrange: Brú na Bóinne in the later Neolithic. (9th December 2021) - Davis, Stephen; Rassmann, Knut
Abstract : The Brú na Bóinne World Heritage Site, Ireland is best known for its megalithic monuments, in particular the great developed passage tombs of Knowth, Dowth, and Newgrange, and its abundance of megalithic art. However, our understanding of the wider Brú na Bóinne landscape has changed beyond all recognition in the last decade owing to the application of modern, non-invasive survey technologies – in particular LiDAR and large-scale geophysical survey – and most recently as a result of the hot, dry summer of 2018 which revealed a series of remarkable cropmarks between Newgrange and the River Boyne. Despite a lack of excavation it can be argued, based on their morphological characteristics, that many of the structures revealed belong within the corpus of late Neolithic ritual/ceremonial structures, including earthen henges, square-in-circle monuments, palisaded enclosures, and pit/post-alignments. These display both extraordinary diversity, yet also commonality of design and architecture, both as a group and with the passage tombs that preceded them. This paper provides an up-to-date survey of the late Neolithic and presumed late Neolithic landscape of Brú na Bóinne. It provides new evidence and new insights from ongoing survey campaigns, suggesting parallels within the British Neolithic but also insular development within some monument classes.